A Route to Synthesize MgAl‐Layered Double Hydroxides via Topotactic Reaction of Mg2+ with Al(OH)3. Issue 25 (6th June 2018) - Li, Yanan; Liang, Dujuan; Feng, Pingping; Yang, Xiaojing
Abstract : We propose an alternative to the synthesis of MgAl‐layered double hydroxides (LDHs) via controlling the topotactic reaction of Mg 2+, OH –, and NO3 – with Al(OH)3 in an aqueous buffer solution (e.g. pH = 9), and the formed MgAl‐LDH crystals are the pseudomorph of the Al(OH)3 precursor but with an increase in volume. Abstract : A new method to synthesize MgAl‐layered double hydroxides (LDHs) is presented by the topotactic reaction of the solid Al(OH)3 precursor with other ions in buffer solution, the formed MgAl‐LDH crystals are the pseudomorph of the precursor with an increase in volume.